2018
DOI: 10.3390/v10010039
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage GC1, a Novel Tectivirus Infecting Gluconobacter Cerinus, an Acetic Acid Bacterium Associated with Wine-Making

Abstract: The Gluconobacter phage GC1 is a novel member of the Tectiviridae family isolated from a juice sample collected during dry white wine making. The bacteriophage infects Gluconobacter cerinus, an acetic acid bacterium which represents a spoilage microorganism during wine making, mainly because it is able to produce ethyl alcohol and transform it into acetic acid. Transmission electron microscopy revealed tail-less icosahedral particles with a diameter of ~78 nm. The linear double-stranded DNA genome of GC1 (16,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 65 publications
2
28
0
1
Order By: Relevance
“…Viral genetic material extraction achieved high concentrations, so it was the basis for deducing that the bacteriophages were constituted of DNA. Visualization by electronic microscopy with DNA extraction allowed the phages to be classified as double-stranded DNA, matching the majority of previous studies of wine or vinegar bacteriophages (Davis et al, 1985;Henick-Kling et al, 1986a,b;Hernández-Magadán, 2007;Dini, 2011Philippe et al, 2018. Despite EcoRI, EcoRV, HinfI, and HindIII endonucleases having been used in similar studies of bacteriophages in dairy products and wine (Moineau et al, 1993;Ackermann, 1998;Spricigo et al, 2013), in our study, the RFLP analysis showed that these enzymes did not digest the genome of the phages isolated.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Viral genetic material extraction achieved high concentrations, so it was the basis for deducing that the bacteriophages were constituted of DNA. Visualization by electronic microscopy with DNA extraction allowed the phages to be classified as double-stranded DNA, matching the majority of previous studies of wine or vinegar bacteriophages (Davis et al, 1985;Henick-Kling et al, 1986a,b;Hernández-Magadán, 2007;Dini, 2011Philippe et al, 2018. Despite EcoRI, EcoRV, HinfI, and HindIII endonucleases having been used in similar studies of bacteriophages in dairy products and wine (Moineau et al, 1993;Ackermann, 1998;Spricigo et al, 2013), in our study, the RFLP analysis showed that these enzymes did not digest the genome of the phages isolated.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, the phages that infected O. oeni belonged to the Tectiviridae family within the polyhedral phages. Although tectiviruses usually infect enteric species, bacilli, and species of the Thermus genus, previous studies have already demonstrated the existence of this family of viruses in wine, such as bacteriophage GC1, a new tectivirus that infects Gluconobacter cerinus in dry white wine-making (Ackermann and DuBow, 1987;Philippe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having established distant orthology with proteins in other Tectiviridae genomes, we assessed the apparent similarity in genome organization between Rhodococcus phage Toil and Streptomyces phages WheeHeim and Forthebois in the broader context of Tectiviridae genome architecture. The genome maps displayed in Figure 4 reveal the previously noted structural genome similarity among the three established tectiviral genera [16], and show that this structural similarity extends to the Rhodococcus and Streptomyces phages. All genomes contain a first genomic segment that appears to have switched orientation in multiple instances, with the family B DNA polymerase as its only identifiable conserved element.…”
Section: Comparative Genomics and Phylogenetic Analysismentioning
confidence: 59%
“…Members of the Betatectivirus genus replicate independently of the host chromosome as linear plasmids and regulate transition to a lytic lifestyle via the host SOS transcription repressor LexA [15]. The Gammatectivirus genus contains only one known member, Gluconobacter phage GC1, which is also temperate and infects the Alphaproteobacterium Gluconobacter cerinus [16].…”
Section: Introductionmentioning
confidence: 99%